Snowmelt detection over the Greenland ice sheet from SSM/I brightness temperature daily variations - Tedesco, Marco (American Geophysical Union, 2007)
We propose a technique for monitoring snowmelt over the Greenland ice sheet between 1992 and 2005 based on the difference between ascending and descending brightness temperatures (DAV) measured either at 19.35- or 37- GHz by the Special Sensor Microwave Imager (SSM/I). Wet snow is detected when both brightness temperatures and DAV values exceed fixed thresholds. Differently from existing techniques, a multi-frequency approach allows detection of wet snow at different depths and intensities, providing a tool for improving climatological and hydrological applications. Air temperature values either recorded by ground based stations or derived from model are used for calibrating and validating the technique. Results are compared with those obtained using backscattering coefficients recorded by the NASA's Quick Scatterometer (QuikSCAT) during an extreme melting event occurring on June 2002. Long-term results show that snowmelt extent has been increasing at a rate of ∼40,000 Km² per year for the past 14 years.